2016
DOI: 10.7705/biomedica.v36i3.2904
|View full text |Cite
|
Sign up to set email alerts
|

Factores relacionados con la adherencia al tratamiento en pacientes con tuberculosis. Pereira, Colombia 2012-2013

Abstract: Affiliation to the health system regime and drug tolerance were objective factors related to adherence to treatment. The social and economic burden of disease is a subjective factor associated with the decision of not adhering to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 16 publications
0
6
0
5
Order By: Relevance
“…This causes challenges for the patients and their families because it exhausts them financially, physically and psychologically. Similar studies have found that the lengthy course of TB challenges both patients and their families financially and emotionally, resulting in non-adherence to treatment [ 29 , 30 ]. This might indicate that the TB treatment protocol needs to be more flexible, so that the treatment schedule is more convenient to patients, allowing them to schedule clinic visits at convenient time.…”
Section: Discussionmentioning
confidence: 93%
“…This causes challenges for the patients and their families because it exhausts them financially, physically and psychologically. Similar studies have found that the lengthy course of TB challenges both patients and their families financially and emotionally, resulting in non-adherence to treatment [ 29 , 30 ]. This might indicate that the TB treatment protocol needs to be more flexible, so that the treatment schedule is more convenient to patients, allowing them to schedule clinic visits at convenient time.…”
Section: Discussionmentioning
confidence: 93%
“…In Argentina, an increased risk of non-adherence with treatment was found in patients who had medical check-ups at hospitals those who had difficulties with transportation costs (Herrero, Ramos, & Arrossi, 2015).The prolonged duration of TB treatment affects patients' adherence due to their daily routine activities. This causes challenges for the patients and their families because it exhausts them financially, physically, and psychologically (Dueñes & Cardona, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…En este estudio, los pacientes sin tratamiento antituberculoso previo tuvieron una mayor probabilidad de éxito del tratamiento, lo cual puede deberse a la presencia de cepas sensibles (13), a factores de cumplimiento del tratamiento (61,62), a las estrategias de educación en salud (63) y a los factores sociales determinantes en salud (64).…”
Section: Discussionunclassified